Retrospective evaluation of a single surgeon’s experience in robot-assisted inguinal repair with the Dexter System™ during the learning curve - Hubert Mignot; Bineta Diack; Juliette Capitaine; Damien Emeriau (International Journal of Abdominal Wall and Hernia Surgery)
BACKGROUND: Robot-assisted transabdominal preperitoneal (r-TAPP) inguinal hernia repair is a safe and feasible approach for hernias of varying etiology. This retrospective study aims to report the feasibility and the learning phase of a single surgeon using the Dexter Robotic System based on operative times while accounting for bilaterality and complexity. MATERIALS AND METHODS: This is a retrospective data analysis of the first 41 consecutive cases of TAPP inguinal hernia repair procedures (25 unilateral and 16 bilateral) that were performed using the Dexter System. The procedures were performed by a single surgeon over 12 months. We report the feasibility of solo surgery in robot-assisted inguinal hernia repair using Dexter. RESULTS: Mean skin-to-skin operative time was 53 min for the unilateral hernia with a significant decrease in operative time from 65 min for the first tertile to 38 min for the third tertile (P < 0.05). For bilateral hernia, the mean skin-to-skin operative time was 81 min with a decrease from 88 min for the first tertile to 71 min for the third tertile, nonstatistically significant. All procedures were conducted fully robotically without any conversion to open surgery or laparoscopy. There were no major complications. Minor postoperative complications were reported in three patients (pain at one trocar site with spontaneous resorption, one trocar hematoma with total resorption at 30 days, and one small seroma). Once the surgeon achieved a consistent level of performance with various types of groin hernia repair, the surgeries were conducted with the surgeon operating independently (solo surgery). CONCLUSIONS: This study demonstrates the feasibility and safety of the robotic approach for inguinal hernia repair using the Dexter system for a surgeon new to robotic techniques. During the initial learning phase observed in the first 41 cases, r-TAPP was associated with an early reduction in operative time.